Representasi Psikologi Sastra pada Film Penyalin Cahaya Karya Wregas Bhanuteja - Azzahra, Rahmani; Solihati, Nani (Universitas Muhammadiyah Surabaya, 2024)
In this study the aims to describe the literary psychological representation of the main character's personality, namely Suryani, in the film